Theoretical aspects of the system of accounting and analytical provision at enterprises for making managerial decisions. (Journal of Economic Research & Business Administration, 2015)
The article comprises the basic principles, requirements and also issues of the system of accounting and analytical provision at the enterprises. The content of the "system of accounting and analytical provision” at the enterprises is investigated. Requirements to the organization of the system of accounting and analytical provision for making managerial decisionsat the enterprise are analyzed. The reasons of improvement of the system of accounting and analytical provision are given. The principles of the effective accounting system development are revealed. Also it is considered that the main reason of low level of controllability at the enterprises is lack of the effective system of accounting and analytical provision
Keywords: system of accounting and analytical provision; managerial decisions; users; requirements; principles; accounting; analysis